2010
DOI: 10.1016/j.jpain.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adolescent Chronic Pain on Functioning: Disentangling the Complex Role of Anxiety

Abstract: A number of adolescents with chronic pain have clinically significant disability across physical, social, and academic activities, and pain severity only explains a portion of the variance in functioning. Thus, it is important to identify therapeutic options to improve adolescents' functioning. In contrast to studies with adults with chronic pain, research in pediatric pain has not consistently found anxiety to be a good predictor of pain-related disability. The present study evaluated pain, anxiety, and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 47 publications
(30 reference statements)
1
61
0
Order By: Relevance
“…A study reported that higher anxiety sensitivity correlates with a higher fear of pain, which is associated with increased pain disability 55 . Another study indicated that pain is related to functioning at a low, but not high, level of anxiety 56 . This finding provides an alternative perspective that anxiety may moderate the relationship between pain and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that higher anxiety sensitivity correlates with a higher fear of pain, which is associated with increased pain disability 55 . Another study indicated that pain is related to functioning at a low, but not high, level of anxiety 56 . This finding provides an alternative perspective that anxiety may moderate the relationship between pain and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…in children with CP-regardless of pain intensity. 16 Even if not directly related to pain, measures of anxiety may still predict painassociated disability. 17 Central to the current study, existing research has shown that anxiety can be mitigated in children with CP through psychological interventions.…”
mentioning
confidence: 99%
“…Greater anxiety sensitivity was associated with lower self-esteem and perceived general and mental health, and with more behavioural problems and family disruption, but did not appear to affect physical functioning (Tsao et al, 2007). In a similar study of 222 adolescents aged 11 to 19 years attending two chronic pain clinics in the UK, Cohen et al (2010) found that in children with low anxiety, level of pain was a good predictor of physical and social function, but that high levels of anxiety prompted poorer function regardless of the level of pain.…”
Section: The Impact Of Chronic Pain On Children and Their Familiesmentioning
confidence: 93%